Factor each of the following expressions into two binomials.

1.x^2-10x+24
2.x^2-12x+27
3.x^2-13x+36
4.x^2-5x-14
5.x^2+x-20
6.x^2-3x-40
7.x^2+2x-48
8.x^2+10x-24
9.x^2-7x-44
10.x^2+x-2
11.x^2+2x+1
12.x^2-x-6

Respuesta :

Answer:

Explanation:

1.
x^2 - 10x + 24
= (x - 6)(x - 4)

2.
x^2 - 12x + 27
= (x - 9)(x - 3)

3.
x^2 - 13x + 36
= (x - 9)(x - 4)

4.
x^2 - 5x - 14
= (x - 7)(x + 2)

5.
x^2 + x - 20
= (x + 5)(x - 4)

6.
x^2 - 3x - 40
= (x - 8)(x + 5)

7.
x^2 + 2x - 48
= (x - 8)(x + 6)

8.
x^2 + 10x - 24
= (x - 2)(x + 12)

9.
x^2 - 7x - 44
= (x - 11)(x + 4)

10.
x^2 + x - 2
= (x + 2)(x - 1)

11.
x^2 + 2x + 1
= (x + 1)(x + 1)

12.
x^2 - x - 6
= (x - 3)(x + 2)